Strategi Bauran Pemasaran 7P pada Industri Perbenihan: Studi Kasus CV Multi Global Agrindo, Kabupaten Karanganyar - Nugraha, Fadhil Adi; Malihatun, Ira; Utami, Inayah Rahmawati Putri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Multi Global Agrindo LP is an agricultural company engaged in the seed sector, particularly plant breeding, and it has sold its products in various regions in Indonesia and abroad. This study aims to increase product sales and customer satisfaction by analyzing the 7P marketing mix at Multi Global Agrindo LP. The research approach used is descriptive. Primary data was collected through interviews with three key respondents, observation, and documentation. Secondary data were sourced from books, scientific articles, and relevant government agency websites. The research results show that the marketing mix strategies implemented were quite good, but still need improvement. Some recommended strategies for Multi Global Agrindo LP, namely increasing prices through a payment system and regular customer discounts, improving product quality and variety, optimizing trend-based digital promotions, expanding e-commerce distribution channels, training human resources to improve service quality, digitizing the ordering process and logistics management, and enhancing packaging by adding QR Codes as proof of product authenticity.